Ubiquitous communications and network computing : First International Conference, UBICNET 2017, Bangalore, India, August 3-5, 2017, Proceedings /: First International Conference, UBICNET 2017, Bangalore, India, August 3-5, 2017, Proceedings. ([2018]) - Unknown
No abstract available